WAWASAN GENDER DALAM EKOLOGI ALAM DAN MANUSIA PERSPEKTIF AL QURAN - Febriani, Nur Arfiyah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
Quranic perspectives on gender-oriented ecology propose eco humanist theocentric theory. This is based on the Quranic description regarding the interconnection and harmonious interaction between a human and him/her self, a human with another human, a human with the universe, and a human with God, regardless male or female. This study employs tafsir maudu’i (thematic), historical-critical-contextual methods, and qualitative approach. The result shows three representations of gender identity, namely biology paired features, various terms referring to men and women interactions, and the balance of femininity and masculinity within every human being. It indicates the possible equal quality of intellectual, emotion and roles in their social life. In addition, the Quran illustrates that both masculine and feminine characteristics have positive and negative sides. This, in fact, has been a debatable notion in the academic world related to men and women stereotyping, which has influenced their social role divisions. While in natural ecology, gender identity is found in three representations, namely biology paired features, pairing in terms of feminine and masculine characteristics/qualities, and pronouns/damir referring to the male and female.